An integrated application of practical blood flow restriction in resistance trained individuals - Martinez, N.; O`Halloran, J.; Kilpatrick, M. W.; Campbell, B. I.; Buckner, S. L. (Journal of Trainology, 2022)
Practical blood flow restriction (PBFR) training has been used as a training technique to induce muscular strength and hypertrophy gains while utilizing lighter loads [= 40% one repetition maximum (1RM)]. It is unclear if PBFR can be incorporated into traditional training programs to alleviate some exposure to heavy loads. Objective: Compare the impact of a traditional resistance training with the addition of PBFR (TRAD + PBFR) to traditional resistance training without PBFR (TRAD) on maximal bench press and leg press strength. Design and Methods: Participants performed full body training for 4 weeks (2-3x/week). PBFR group performed 62% of sets blood flow restricted at 30% 1RM while the TRAD group performed all sets at an intensity of >70% 1RM. Results: Twenty-one resistance trained individuals (= 1 year resistance training) completed the study. For bench press strength, there was no group (TRAD + PBFR vs. TRAD) by time (pre vs. post) interaction (BF10 = 0.32). However, there was a main effect for time (BF10 = 24.04). The TRAD + PBFR group increased strength from 99 ± 29 to 106 ± 23 kg and the traditional training condition increased from 111 ± 27 to 117 ± 24kg. For leg press strength, there was no interaction (BF10 = 0.83). However, there was a main effect for time, with both conditions increasing strength. For the PBFR group strength increased from 372 ± 61 to 423 ± 76 kg and the TRAD group increased strength from 354 ± 87 to 434 ± 96kg. Conclusion: TRAD + PBFR elicited similar strength adaptations compared to TRAD. PBFR may provide a means to exposing the muscle and connective tissue to less overall mechanical stress when incorporated into a traditional heavy resistance training program.